Antecedents of Overtime Work: The Case of Junior Academics - Irina Frei; Christian Grund (Institute of Labor Economics (IZA), 2017)
Despite the ongoing public debate about precarious working conditions in academia, there is only little evidence on working hours and overtime work for the group of (non-tenured) junior academics. By using unique longitudinal survey data on the occupational situation and careers of doctoral students and doctorate holders in STEM fields in Germany, we explore potential antecedents of overtime. We find that overtime hours are less pronounced among firm employees holding a doctorate and among postdocs than they are among doctoral students. This result holds in the cross-section and also when examining status changes (from doctoral student to postdoc or to firm employee holding a doctorate) in difference-in-differences estimations. In contrast to firm employees, overtime hours are considerably positively associated with part-time contracts for doctoral students. Furthermore, our results reveal that individuals' career orientation is positively associated with extra hours. In contrast, individuals with family responsibilities and a stronger preference for leisure time spend significantly fewer hours at work.
Keywords: I23; J22; M51; 330; working time; overtime; part-time employment; academia